Assessment Techniques to Improve Listening and Speaking skills in Second year English students, URACCAN, I semester, 2023 - Aguilar Rosales, Josseling Isela; Rodríguez Rodríguez, Freddy Josué (Nicaragua, 2023)
Estrategias utilizadas para incentivar a los estudiantes de segundo año en uraccan
Incluye: bibliografía, índice
Col. Educ.
Keywords: 1 . EDUCACIÓN 2. INGLES 3. ESTRATEGIAS DOCENTES